Effect of Hydrothermal Pretreatment Time on Biochemical Recovery and Hydrogen Production from Lignocellulosic Feedstocks - Amer Rouabhia; Carlos José Álvarez-Gallego; Luis Alberto Fernández-Güelfo (Applied Sciences)
This study examines the impact of hydrothermal pretreatment operation time (10, 20, and 30 min) on the following four lignocellulosic feedstocks with different lignin content: sugar beet pulp (SBP), brewers spent grain (BSG), orange peel (OP), and rice husk (RH). The objective of pretreatment is twofold, as follows: (1) to enhance the organic matter solubilization and the release of value-added bioproducts, such as total reducing sugars (TRS), total proteins (PR), and volatile fatty acids (VFAs); and (2) to improve VFA and hydrogen production during a subsequent stage of acidogenic anaerobic digestion (Dark Fermentation, DF). In this context, OP reported the highest overall yields across all pretreatment durations. Specifically, at 30 min, it achieved a maximum solubilization of 57.3 gO2/L in terms of soluble chemical oxygen demand (sCOD), 19.1 gTRS/L and 20.6 gPR/L. Regarding VFA and hydrogen production via dark fermentation, the best results were obtained with SBP pretreated for 20 and 30 min, yielding 15.1 g H-Ac/L and 97.5 mL H2 (n.c.)/g (d.m.), respectively. BSG displayed an intermediate performance, whereas RH consistently showed the lowest yields across all evaluated parameters, primarily due to its high lignin content. These findings highlight the pivotal role of pretreatment duration in the valorization of lignocellulosic biomasses, primarily aimed at the recovery of high-value-added biochemicals and biofuels, such as hydrogen, thereby supporting the development of integrated biorefinery systems.